2023
DOI: 10.1002/mc.23636
|View full text |Cite
|
Sign up to set email alerts
|

CDK10 suppresses metastasis of lung adenocarcinoma through inhibition of the ETS2/c‐Raf/p‐MEK/p‐ERK signaling loop

Xiujuan Zhang,
Yu Zhao,
Ruzetuoheti Yiminniyaze
et al.

Abstract: The repertoire of aberrant signaling underlying the pathogenesis of lung adenocarcinoma remains largely uncharacterized, which precludes an efficient therapy for these patients, especially when distant metastasis occurs. Cyclin‐dependent kinase 10 (CDK10) has been reported to modulate the progression of malignant tumors; however, contradictory effects have been found among different types of malignant tumors. In the present study, we found that CDK10 was downregulated in lung adenocarcinoma compared with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
(85 reference statements)
1
2
0
Order By: Relevance
“…Ectopic expression of CDK10 inhibited cell proliferation and migration in gastric cancer cells, and vice versa ( 26 ). Our study showed that CDK10 knockdown significantly increased cell growth and migration in lung cancer cells, which was consistent with a recent study ( 8 ). DNA double strand breaks (DSBs) can lead to cancer cell death after ionizing radiation, and γ-H2AX foci is a biomarker for DSBs ( 27 ), while radiosensitivity cell lines showed slower rates of γ-H2AX foci depletion ( 28 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Ectopic expression of CDK10 inhibited cell proliferation and migration in gastric cancer cells, and vice versa ( 26 ). Our study showed that CDK10 knockdown significantly increased cell growth and migration in lung cancer cells, which was consistent with a recent study ( 8 ). DNA double strand breaks (DSBs) can lead to cancer cell death after ionizing radiation, and γ-H2AX foci is a biomarker for DSBs ( 27 ), while radiosensitivity cell lines showed slower rates of γ-H2AX foci depletion ( 28 ).…”
Section: Discussionsupporting
confidence: 94%
“…CDK10 inhibited lung cancer cell growth and metastasis by inhibition of the ETS2/c-Raf/p-MEK/p-ERK signaling loop ( 8 ). The evidence was well established that the JNK/c-Jun signaling pathway was associated with cell proliferation, migration, invasion, and radioresistance in various cancers ( 20 , 21 , 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation